1998
DOI: 10.1046/j.1469-8137.1998.00893.x
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthate costs associated with the utilization of different nitrogen–forms: influence on the carbon balance of plants and shoot–root biomass partitioning

Abstract: The photosynthate costs of processes (amino acid and protein synthesis and turnover, and pH regulation) associated with the utilization of nitrate (NO $ − ), ammonium (NH % + ) or glutamine (Gln) for plant growth were estimated. Based on these estimates, the effects of these forms of nitrogen (N) on the carbon balance of plants and on shoot-root biomass allocation were evaluated. The results indicated that NO $ − as an N source for plant growth is not substantially more expensive to utilize than either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
2
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 58 publications
4
69
2
2
Order By: Relevance
“…For this to be the case, C utilization in processing N must be of a magnitude which could affect dry matter partitioning between shoot and root. There is general agreement that for higher plants usually 25-65% of C fixed in photosynthesis is lost via respiration (Byrd, Sage & Brown 1992;Amthor 1994;Zerihun et al 1998). Zerihun et al (1998) calculated the photosynthetic costs associated with the utilization of NO 3 -, NH 4 + or glutamine as N source and concluded that costs were similar with the different N forms particularly in the longer term when costs due to turnover of protein (primarily soluble protein) dominate the total cost of N utilization.…”
Section: The Mechanism(s) Of N Concentration and Form Effects On S : Rmentioning
confidence: 99%
See 2 more Smart Citations
“…For this to be the case, C utilization in processing N must be of a magnitude which could affect dry matter partitioning between shoot and root. There is general agreement that for higher plants usually 25-65% of C fixed in photosynthesis is lost via respiration (Byrd, Sage & Brown 1992;Amthor 1994;Zerihun et al 1998). Zerihun et al (1998) calculated the photosynthetic costs associated with the utilization of NO 3 -, NH 4 + or glutamine as N source and concluded that costs were similar with the different N forms particularly in the longer term when costs due to turnover of protein (primarily soluble protein) dominate the total cost of N utilization.…”
Section: The Mechanism(s) Of N Concentration and Form Effects On S : Rmentioning
confidence: 99%
“…There is general agreement that for higher plants usually 25-65% of C fixed in photosynthesis is lost via respiration (Byrd, Sage & Brown 1992;Amthor 1994;Zerihun et al 1998). Zerihun et al (1998) calculated the photosynthetic costs associated with the utilization of NO 3 -, NH 4 + or glutamine as N source and concluded that costs were similar with the different N forms particularly in the longer term when costs due to turnover of protein (primarily soluble protein) dominate the total cost of N utilization. It has been estimated that 25-60% of total respiratory loss is due to protein turnover (Penning de Vries 1975;Barneix et al 1988; de Visser, Spitter & Bouma 1992).…”
Section: The Mechanism(s) Of N Concentration and Form Effects On S : Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Embryogenic cultures grown without L-glutamine must synthesize this amino acid from the nitrogen sources available in the medium. This can be seen as an energetic disadvantage in comparison to PEM cultures which can take up the L-glutamine directly from the medium [25,26], although energy is not a limiting factor if sucrose is supplied in the medium. The beneficial effect of L-glutamine on growth of cell cultures has been shown for several conifer species including Pseudotsuga menziesii (Mirb.)…”
Section: Morphological and Developmental Characterization And Nitrogmentioning
confidence: 99%
“…However, the N form is rarely considered. Zerihun et al [73] noted that there are significantly different C costs associated with assimilating nitrate, ammonium, or glutamine, and that the physical location and time of assimilation could also have effects. For example, malate derived from photorespiration acts as a source of reducing power for nitrate, where assimilation occurs in the leaves during the light period, without significantly affecting carbon fixation rates [23].…”
Section: Nutrient and Water Availabilitymentioning
confidence: 99%